2006
DOI: 10.1211/jpp.58.10.0007
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidaemic and antiplatelet activity of phenoxyacetic acid derivatives related to α-asarone

Abstract: The phenoxyacetic acid derivatives 1-6 [2-methoxy-4-(2-propenyl)phenoxyacetic acid (1); 2-methoxy-5-nitro-4-(2-propenyl)phenoxyacetic acid (2); methyl 2-methoxy-4-(2-propenyl)phenoxyacetate (3); ethyl 2-methoxy-4-(2-propenyl)phenoxyacetate (4); methyl 2-methoxy-5-nitro-4-(2-propenyl)phenoxyacetate (5); ethyl 2-methoxy-5-nitro-4-(2-propenyl)phenoxyacetate (6)] related to alpha-asarone have been reported previously as hypolipidaemic agents in diet-induced hyperlipidaemic mice. We have aimed to expand the pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The nonionic detergent, Triton WR‐1339, has been used widely to block the uptake of triacylglycerol‐rich lipoproteins from plasma by peripheral tissues to produce acute hyperlipidaemia in animal models, which are often used for a number of objectives, in particular for screening natural or chemical hypolipidaemic drugs 1,20,21,28 . Experimental evidence supports the concept that Triton WR‐1339 physically alters very low density lipoproteins (VLDL), rendering them refractive to the action of lipolytic enzymes of blood and tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonionic detergent, Triton WR‐1339, has been used widely to block the uptake of triacylglycerol‐rich lipoproteins from plasma by peripheral tissues to produce acute hyperlipidaemia in animal models, which are often used for a number of objectives, in particular for screening natural or chemical hypolipidaemic drugs 1,20,21,28 . Experimental evidence supports the concept that Triton WR‐1339 physically alters very low density lipoproteins (VLDL), rendering them refractive to the action of lipolytic enzymes of blood and tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Triton WR‐1339 (an oxyethylated tertiary octyl phenol formaldehyde polymer), one of the well known nonionic detergents, has been used widely to produce acute hyperlipidaemia in animal models 20,21 . Thus, this study was designed to investigate a potential hypolipidaemic effect of (PhSe) 2 on Triton WR‐1339‐induced acute hyperlipidaemia in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Further study indicated that activities of α -asarone in various animal seizure models [14] and against noise-stress effect [15] might be essentially accounted for by antioxidant properties. In addition, the hypolipidaemic [1620] and radioprotective effects [21] of α -asarone were also been reported. Besides, β -asarone, which has toxic and sterilizing effects, shows potential for stored-product pest control [22].…”
Section: Introductionmentioning
confidence: 99%
“…It is an odorless and tasteless compound with good antioxidant power and is considered to be nontoxic [1]. Eugenoxyacetic acid, 5-nitroeugenoxyacetic acid, and their methyl, ethyl esters are known to exhibit hypolipidaemic and antiplatelet activity and thus appear to be promising for the treatment of human hyperlipidaemia and thrombotic diseases [2][3][4]. In addition, several modified side chain eugenoxyacetic acids have been shown to exhibit antiviral and antimycobacterial activities [5,6].…”
Section: Introductionmentioning
confidence: 99%